The quality of community facilities in section 18 & section 19, Shah Alam / Norhaida Saari - Saari, Norhaida (2010)
Facilities are an essential tool that must be provided in every housing scheme area. The common facilities that usually available are school, grocery shop, playground, open space, clinic and mosque. Residents who act as a user really need those facilities in order to fulfill their social needs and also to ensure the effectiveness of their daily routine. Therefore the provision of the facilities must be enough and fulfill the entire standard required. However, there are still problems happen regarding on the provision of the facilities and in fact the existing facilities condition does not really satisfactory. The aim of this research is to identify the quality of the facilities in Section 18 and Section 19, Shah Alam. Besides to know the important factors contributing to its quality, this research will revolve around the differences between residents both sections in term of their perception and utilization of the facilities. So, in order to achieve those aims, the satisfaction level will be measured and the perception plus their opinion will be obtained through primary data by distributing the questionnaire survey and interview. Any other related information regarding this research is gathered through available secondary data. Sources of data are gathered by the previous researches and related journals. It is hoped that this research will be able to reveal the quality of the facilities within both sections and clearly explain the factors contributing facilities towards the good quality. Other than that, it is hoped too that this research could clearly differentiate the perception of residents in both sections as well. Finally, whatever the finding and the conclusion are, the facilities are the complementary tools that need to be provided and well managed so that the quality required can be achieved and therefore increase the quality of life of the residents